The edaphic and climatic effects on production and wine quality of Cabernet Sauvignon in the Lower Olifants River region - Bruwer, Rachel Jacoba (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2010.